Le Pen and the FN: an analysis of France's changing populism - Pierce, Marlene Kathryn Lee (Kansas State University, 2019)
After her defeat in 2016 French presidential election, Marine Le Pen would not back down from the political spotlight. Instead, Le Pen would utilize the momentum she gained during the election to solidify herself as a formidable political figure and take her party to the next level. Nearly a year after her defeat she would give a speech in Lyon, France that establishes her place in the political milieu by rebranding her party from the Front National to Rassemblement National, or translated, National Rally. This thesis examines Marine Le Pen’s Lyonnaise address. Using a mixed method of Leff’s rhetorical reading, ideological criticism, and elements of visual and presidential rhetorical methods, this thesis examines two main themes in Le Pen’s Lyonnaise address: 1) a shift in focus from Jean-Marie to Marine Le Pen utilizing the persona of each and 2) an internationalizing of the previously nationalistic Front National. This analysis thus offers a detailed depiction of how populism is defined and redefined. As well, it clarifies the contours of populism encapsulated by the FN. The thesis then looks at the history of the FN party in context of how the persona of its leaders shaped the party’s advocacy. Finally, the last thing that is examined is the ways in which this speech indicates an internationalizing FN and then the thesis offers broader implications and conclusions. This work offers important insight to how populist parties, which are notoriously volatile in their support, can stabilize and grow. It also highlights an increasing shift in isolated populist groups shifting their scope and operating on an international level. This research can add to existing literature and offer a unique look into a previously untranslated artifact.
Keywords: Populism; Marine Le Pen; Transnational Populism; Persona; Rhetorical Reading